Les approvisionnements morutiers de la Guadeloupe durant la Seconde Guerre mondiale - Alamkan, Myriam (The Northern Mariner / Le marin du nord, 2020)
During the Second World War, isolated in the absence of commercial relations with France, Guadeloupe used the peculiarities of its status as a French colony to continue to provide its population with essential cod from Saint-Pierre and Miquelon and Newfoundland and Labrador without its own commercial fleet. Although officially linked to Vichy France, Guadeloupe took advantage of the improbable agreements signed with the United States and, when administered by Free France, it collaborated with Newfoundland. To alleviate the shortage, the Guadeloupe authorities for the first time promoted the consumption of fresh fish as a substitute for cod.